Clinical profile and histo-pathological profile of peri-ocular lesions - Raina, Bhavani; Mahajan, Sachit; Kai, Sanjay (International Journal of Research in Medical Sciences, 2022)
Background: Eyelid carcinoma is the most common malignant lesion of eyelid region, and may involve either skin or tarus or inner layer of eyelid. The most common primary eyelid malignancy is basal cell carcinoma (BCC), squamous cell carcinoma (SqCC), sebaceous gland carcinoma (SGC), malignant melanoma, and Merkel cell carcinoma. The prevalence of these malignant lesion vary according to the geographical region. The aim of the study was to correlate the diagnosis of various peri-ocular lesions with the histological diagnosis. Methods: This prospective longitudinal study was conducted over a period of two years in patients with ocular and periocular skin lesions. All the patients underwent incision biopsy of the lesion biopsy material was sent for histopathology examination. The histological profile of the tumour was confirmed by the report. Results: The mean age in our study was 32.7±18.4 years with age range of 18 to 78 years, with 108 females (54%) and 92 males (46%). 173 (86.5%) were benign lesions and 27 (13.5%) were malignant lesions. Right eye was involved in more cases (n=104, 52%) as compared to left eye (n=96, 48%). Upper eye lid was involved more (n=102, 51%) than lower eye lid (n=98, 49%). Epidermal cyst was most common lesion (n=43, 21.5%), followed by dermoid cyst (n=28, 14%). Sebaceous gland carcinoma was most (n=15, 7.5%) malignant lesion, followed by basal cell carcinoma (n=7, 3, 5%). Conclusions: All excised eyelid lesions must be submitted for histopathologic confirmation to achieve 100% accuracy in diagnosis and treatment. Early diagnosis remains essential for adequate functional and cosmetic lid reconstruction.